The Influence of Foreign Investors on the Efficiency of the Saudi Stock Market - Abdullah Alesmaiel; Suzanne Fifield; Justin Hof (Emerging Markets Journal)
This article examines whether the level of weak-form efficiency of the Saudi stock market increased following liberalization in June 2015 when the market was opened up to foreign institutional investors. The results revealed that most sample companies and the market index did not follow a random walk over the sample period. However, the random walk hypothesis was not rejected after opening the market to foreign investors. This evidence implies that the steps taken by policy-makers to liberalize the Saudi stock market appear to have had a positive impact on the level of market efficiency.